Effectiveness of Agri-Clinics in Promoting Paid Extension Services Among Farmers - Shekar, S. Chandra; Bahal, R.; Padaraia, Rabindra Nath (Indian Journal of Extension Education, 2013)
This study was conducted in Uttar Pradesh to evaluate the farmers' perceived effectiveness of paid extension services  provided by Agri Clinic entrepreneurs. Study found that the effectiveness was high among the beneficiary farmers. About  fifty per cent respondents perceived that the paid extension services were moderately effective while the rest perceived  them to be highly effective. Among the correlates, annual income, social participation, farm machinery owned were  negatively and significantly associated. Regression analysis of effectiveness index scores revealed the positive  contribution of age, education, farm size and negative contribution of farming experience, annual income and social  participation. Among the four components, the contribution of extent of adoption and farmers' satisfaction was very high  in farmers' perceived effectiveness of paid extension services provided by Agri Clinic entrepreneurs.
Keywords: Agri clinic; adoption; yield; profit; farmers' satisfaction; extension effectiveness index